The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2017
DOI: 10.2147/copd.s141976
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of pulsed versus continuous oxygen delivery using realistic adult nasal airway replicas

Abstract: BackgroundPortable oxygen concentrators (POCs) typically include pulse flow (PF) modes to conserve oxygen. The primary aims of this study were to develop a predictive in vitro model for inhaled oxygen delivery using a set of realistic airway replicas, and to compare PF for a commercial POC with steady flow (SF) from a compressed oxygen cylinder.MethodsExperiments were carried out using a stationary compressed oxygen cylinder, a POC, and 15 adult nasal airway replicas based on airway geometries derived from med… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
44
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 29 publications
(59 citation statements)
references
References 26 publications
2
44
0
1
Order By: Relevance
“…In Chen et al, 10 testing was limited to a single POC evaluated at 2 integer pulse settings, one high (6) and one low (2). It was found that intersubject variability among 15 airway geometries had only a small (Ͻ5% coefficient of variation) impact on volume-averaged F IO 2 values.…”
Section: Selection Of a Representative Airway Replicamentioning
confidence: 99%
See 4 more Smart Citations
“…In Chen et al, 10 testing was limited to a single POC evaluated at 2 integer pulse settings, one high (6) and one low (2). It was found that intersubject variability among 15 airway geometries had only a small (Ͻ5% coefficient of variation) impact on volume-averaged F IO 2 values.…”
Section: Selection Of a Representative Airway Replicamentioning
confidence: 99%
“…It was found that intersubject variability among 15 airway geometries had only a small (Ͻ5% coefficient of variation) impact on volume-averaged F IO 2 values. 10 Therefore, it was deemed reasonable to use only a single representative replica for comparative testing in the present work. A single replica was selected on the criterion that the volume-averaged F IO 2 value obtained by using this replica (for either continuous flow oxygen or pulse flow) was closest to the average value obtained across the set of 15 replicas.…”
Section: Selection Of a Representative Airway Replicamentioning
confidence: 99%
See 3 more Smart Citations